2011
DOI: 10.1007/s11033-011-1319-8
|View full text |Cite
|
Sign up to set email alerts
|

PTGS2 (COX2) −765G>C gene polymorphism and risk of sporadic colorectal cancer in Iranian population

Abstract: Colorectal cancer (CRC) is one of the leading cancers worldwide. Through genome wide association studies, several single nucleotide polymorphisms scattered in the genome emerged to be influential in the development of sporadic CRC in some populations. However, replicative studies failed to prove a particular SNP-CRC association in populations and ethnic groups. Cyclooxygenase-2 (PTGS2) is a crucial enzyme involved in the metabolism of prostaglandins. The aim of this replicative study is to investigate the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…The characteristics of the selected studies are summarized in Table 1 and Table S1. The 13 studies analyzed the following polymorphism: PTGS1 rs3842787 (n = 3) [4]–[6], PTGS2 rs5275 (n = 8) [5], [7][13], PTGS2 rs20417 (n = 7) [4], [8]–[10], [12], [14], [15], PTGS2 rs689466 (n = 3) [8], [11], [12], and rs2745557 (n = 3) [5], [9], [16].…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the selected studies are summarized in Table 1 and Table S1. The 13 studies analyzed the following polymorphism: PTGS1 rs3842787 (n = 3) [4]–[6], PTGS2 rs5275 (n = 8) [5], [7][13], PTGS2 rs20417 (n = 7) [4], [8]–[10], [12], [14], [15], PTGS2 rs689466 (n = 3) [8], [11], [12], and rs2745557 (n = 3) [5], [9], [16].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a final total of 38 case-control studies in 37 articles which met our inclusion criteria were identified, including 10814 cases and 16174 controls. Among 38 cases and controls, there were 20 case-controls of Asians (Hamajima et al, 2001;Koh et al, 2004;Liu et al, 2006;Guo et al, 2007;Tan et al, 2007;Chiang et al, 2008;Lin et al, 2008;Saxena et al, 2008;Ueda et al, 2008;Xing et al, 2008;Xu et al, 2008;Tang et al, 2009;Upadhyay et al, 2009;Zhao et al, 2009;Mittal et al, 2010;He et al, 2011;Chang et al, 2012;Li et al, 2012;Shin et al, 2012), 11 of Caucasians (Cox et al, 2004;Pereira et al, 2006;Hou et al, 2007;Moons et al, 2007;Sitarz et al, 2008;Andersen et al, 2009;Hoff et al, 2009;Iglesias et al, 2009;Kristinsson et al, 2009;Pereira et al, 2010;Daraei et al, 2012), 4 of Americans (Ulrich et al, 2005;Gunter et al, 2006;Gong et al, 2009;Thompson et al, 2009), and 1 of Africans (Bye et al, 2011), and 2 of Mixed (Bye et al, 2011;Wang et al, 2012). 9 investigated gastric cancer (Liu ...…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
“…9 investigated gastric cancer (Liu et al, 2006;Pereira et al, 2006;Hou et al, 2007;Saxena et al, 2008;Sitarz et al, 2008;Tang et al, 2009;Li et al, 2012;Shin et al, 2012), 16 investigated colorectal cancer (Hamajima et al, 2001;Cox et al, 2004;Koh et al, 2004;Ulrich et al, 2005;Gunter et al, 2006;Xing et al, 2008;Ueda et al, 2008;Andersen et al, 2009;Gong et al, 2009;Hoff et al, 2009;Iglesias et al, 2009;Thompson et al, 2009;Pereira et al, 2010;Daraei et al, 2012;Wang et al, 2012), 3 investigated oral cancer (Chiang et al, 2008;Lin et al, 2008;Mittal et al, 2010), 6 investigated esophageal cancer (Guo et al, 2007;Moons et al, 2007;Kristinsson et al, 2009;Upadhyay et al, 2009;Bye et al, 2011), and 4 investigated pancreatic cancer and hepatocellular carcinoma (HCC) (Xu et al, 2008;Zhao et al, 2009;He et al, 2011;Chang et al, 2012). Of these articles, 18 studies were performed in HB (Hamajima et al, 2001;Cox et al, 2004;Gunter et al, 2006;Pereira et al, 2006;…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
“…Molecular and genetic study can play a key role in the detection of CRC because genetic alterations are the main causes of colorectal neoplasia 10. Some studies have already tried to show the correlation between various SNP and CRC 111213. One thing is obvious enough that stool-based tests are a noninvasive method, but, in contrast, structural exams are invasive 8.…”
Section: Introductionmentioning
confidence: 99%